Flexible bandpass filter with silver conductive layer for GPS, ISM, PCS, LTE and WLAN applications. (2021) - Vineetha, K.V.; Siva Kumar, M.; Madhav, B.T.P.; Rao, M.C.
Abstract: In this work a flexible wide bandpass filter with silver conducting layer on polyimide substrate have been used. The placed silver layer has good mechanical and electrical flexibility. Measured results are showing the fractional bandwidth value of 44% with return loss value of below −15 dB and insertion loss of −1dB. At various bending conditions, the proposed bandpass filter showing constant performance value. The formed silver layer also presents good adhesion with polyimide layer. Surface roughness and skin depth of the silver layer also analysed in order to know the variation in the performance value of the proposed bandpass filter. The conformality of proposed bandpass filter across 15 0, 30 0, 45 0, 60 0 and 90 0 bending are analysed and found negligible variation in the performance characteristics. Prototyped microstrip bandpass filter results are measured using ANRITSU-MS2037C combinational analyser and found suitable validation with simulation results.